Unemployment youths in the Ukhrul district of Manipur with reference to Tangkhul tribe between 2014 to 2017. - Ningthilsana, Chingangbam; Shukla, Arvind Shanker (South Eastern European Journal of Public Health, 2025)
This paper is mainly focus on educated youth which are unemployed due to the education system or lack of skills that they cannot compete in the open environment. So, the research is done in the Ukhrul district of Manipur which is mainly inhabited by the Tangkhul tribe. Manipur is also very high unemployment rate in the country, and the state government also struggling for this situation. State government with the help of central government trying to tackle this situation by bring schemes sponsored by central and state government. For this paper I used both primary and secondary data from various sources. In this paper the government also trying to look alternative means like start up, enterprenuers, etc.